Fiber fueled : the plant-based gut health program for losing weight, restoring your health, and optimizing your microbiome - Bulsiewicz, Will (Avery, an imprint of Penguin Random House, 2020)
"A bold new plant-based plan that challenges popular keto and paleo diets, from an award-winning gastroenterologist. The benefits of restrictive diets like paleo and keto have been touted for more than a decade, but as renowned gastroenterologist Dr. Will Bulsiewicz, or "Dr. B," illuminates in this groundbreaking book, the explosion of studies on the microbiome makes it abundantly clear that eliminations are in fact hazardous to our health. What studies clearly now show--and what Dr. B preaches with his patients--is that gut health is the key to boosting our metabolism, balancing our hormones, and taming the inflammation that causes a host of diseases. And the scientifically proven way to fuel our guts is with dietary fiber from an abundant variety of colorful plants. Forget about the fiber your grandmother used to take--the cutting-edge science on fiber is incredibly exciting. As Dr. B explains, fiber energizes our gut microbes to create powerhouse postbiotics called short-chain fatty acids (SCFAs) that are essential to our health. SCFAs are scientifically proven to promote weight loss, repair leaky gut, strengthen the microbiome, optimize the immune system, reduce food sensitivities, lower cholesterol, reverse type 2 diabetes, improve brain function, and even prevent cancer. Restrictive fad diets starve the gut of the critical fiber we need, weaken the microbes, and make our system vulnerable. As a former junk-food junkie, Dr. B knows firsthand the power of fiber to dramatically transform our health. The good news is that our guts can be trained. Fiber-rich, real foods--with fruits, vegetables, whole grains, seeds, nuts, and legumes--start working quickly and maintain your long-term health, promote weight loss, and allow you to thrive and feel great from the inside out. With a 28-day jumpstart program with menus and more than 65 recipes, along with essential advice on food sensitivities, Fiber Fueled offers the blueprint to start turbocharging your gut for lifelong health today"--